The effect of cognitive behavioral therapy in managing blood-injury-injection phobia (BIIP) in a biomedical laboratory setting - Putri Djamilah Wahidah; Tika Dwi Tama; Dea Aflah Samah; Dewa Bagus Prasetayo; Nailyaa Faza Hendrawan (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2025)
Purpose – This study aimed to examine the effect of Cognitive Behavioral Therapy (CBT) in reducing vasovagal responses among individuals with BIIP, as measured by indicators of fear severity, perception, heart rate, and oxygen saturation. Design/methods/approach – This study employed a pre-experimental design using a one-group pretest–posttest approach with purposive sampling. The sample consisted of 24 undergraduate students enrolled in a public health program. Four variables were examined: fear severity, perception, heart rate, and oxygen saturation. Data were analyzed using univariate analysis through frequency distribution and tabulation. Bivariate analysis was conducted using the Wilcoxon Signed Rank Test to determine the significance of therapeutic outcomes by comparing pretest and posttest results. The Kruskal–Wallis test with post hoc analysis was also applied to identify which CBT sessions were most effective in reducing BIIP-related anxiety symptoms. Findings – Of the four variables examined, fear severity and perception showed p-values greater than 0.05, indicating non-significant changes following the intervention, although percentage improvements were observed. Heart rate demonstrated a statistically significant effect, with a p-value of 0.028 (< 0.05), indicating a significant improvement, particularly during sessions four and five. In contrast, oxygen saturation yielded a p-value of 0.485, suggesting no statistically significant improvement across sessions one through five. Research implications/limitations – These findings suggest that CBT may be particularly effective in modulating physiological responses associated with BIIP in educational laboratory settings. However, the absence of a control group, the relatively small sample size, and variability in session attendance limit the generalizability of the results. Future studies employing controlled experimental designs and larger samples are recommended to strengthen causal inferences. Originality/value – This study contributes original empirical evidence by integrating psychological and physiological indicators to evaluate the effectiveness of CBT for BIIP within a biomedical laboratory context. The findings offer practical insights for implementing CBT-based interventions to enhance student safety and preparedness during laboratory-based blood-related procedures.